The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1360-6441.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Communities of practice: 
Legitimacy not choice

Abstract: Communities of practice has emerged as an alternative to other current sociolinguistic models such as speech communities and social networks, particularly in the area of language and gender. The valorization of non‐linguistic behaviours as adding further explanatory power to sociolinguistic models is timely: it has often been implicit in linguistic study (through ethnography) but rarely been given recognition. However, the types of self‐constituting communities of interest to sociolinguists are not the same as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 28 publications
(46 reference statements)
0
69
0
3
Order By: Relevance
“…By looking into convergent and accommodative mimetic moves in various units of analysis in our dataset, we hope to have demonstrated that accommodative mimesis represents how conventionalisation and ritualisation are set into action in the lives of communities of practice (Davies, 2005). Such ephemeral moves towards conventionalisation and ritualisation differ from a) actual conventionalisation and ritualisation, which produce long-lasting interactional practices, and b) accommodative moves in socially established practice types.…”
Section: Resultsmentioning
confidence: 92%
“…By looking into convergent and accommodative mimetic moves in various units of analysis in our dataset, we hope to have demonstrated that accommodative mimesis represents how conventionalisation and ritualisation are set into action in the lives of communities of practice (Davies, 2005). Such ephemeral moves towards conventionalisation and ritualisation differ from a) actual conventionalisation and ritualisation, which produce long-lasting interactional practices, and b) accommodative moves in socially established practice types.…”
Section: Resultsmentioning
confidence: 92%
“…Em contexto de estágio, as críticas apontadas às CoP referem-se, sobretudo, à hierarquia existente no seu seio e às inevitáveis relações de poder estabelecidas, bem como à falta de uma distinção perfeitamente inequívoca entre uma posição periférica e marginal face à CoP (Davies, 2005;Hall, 2017;Mitra, 2008). Uma hierarquia fortemente estabelecida no seio da CoP pode originar um processo de ensino-aprendizagem unidirecional, no qual a transmissão de conhecimento é apenas feita por parte dos membros mais antigos e os EE são vistos como recetáculos de informação, ou seja, a posição de poder dentro de uma CoP é valorada mediante o conhecimento que cada participante detém.…”
Section: Comunidades De Prática -Que Limitações?unclassified
“…Davies (2005) refere que não existe uma distinção clara entre a participação periférica e marginal, parecendo apenas que a alguns participantes lhes é dada a escolher a forma de participação e outros são, simplesmente, marginalizados. O mesmo autor acrescenta que, no caso de o acesso à CoP não estar dependente da aprendizagem e do envolvimento nas suas práticas, mas apenas da aceitação daqueles que possuem poder e estatuto dentro da CoP, a situação de aprendizagem afasta-se do que é desejável e adequado.…”
Section: Comunidades De Prática -Que Limitações?unclassified
“…A member's social identity is linked to their position within a group, making the CofP approach highly compatible with constructivist approaches, which stress the 'discursive', 'emergent', and 'positional' nature of identity (Bucholtz and Hall, 2005). This idea of a trajectory from periphery to core, from ignorance to 'competence and experience' (Wenger 1998: 138) is somewhat idealised in the original accounts of CofP (Lave and Wenger, 1991;Wenger, 1998), and Davies (2005) successfully shows how this movement might be unwanted by some members of a CofP, and impossible for others.…”
Section: Communities Of Practicementioning
confidence: 99%
“…In this way, institutional groups, such as those in some workplaces, may not be the best examples of CofPs (King 2014: 63) because the participants may not have much say over how they are going to respond to 'their conditions, and therefore to their enterprise' (Wenger 1998: 79 -emphasis in original). This local negotiation of joint enterprise is even more necessary in 'self-constituted' groups (Davies, 2005) where there are fewer guidelines directing joint enterprise, such as reading groups.…”
Section: Communities Of Practicementioning
confidence: 99%